2010
DOI: 10.1057/jt.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

An analytical study of complaining attitudes: With reference to the banking sector

Abstract: Service failures in retail banking tend to have a negative impact on service quality and, consequentially, on customer satisfaction. This heightens the need for effective complaint handling. This article attempts to profi le and segment bank customers on the basis of complaining attitudes and perception of complaint handling mechanisms (of banks). Cluster analysis suggested that bank customers can be divided into four segments: non-complainers, switchers, prompt complainers and positive thinkers . Further, AHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…customer protection agencies or lawyers. In support of this categorisation, Siddiqui and Tripathi's (2010) contemporary research in the banking sector reveals similar findings.…”
Section: Fundamentals Of Customer Satisfaction With Complaint Handlingsupporting
confidence: 62%
“…customer protection agencies or lawyers. In support of this categorisation, Siddiqui and Tripathi's (2010) contemporary research in the banking sector reveals similar findings.…”
Section: Fundamentals Of Customer Satisfaction With Complaint Handlingsupporting
confidence: 62%
“…For instance, Siddiqui and Tripathi (2010) found four segments of customers in terms of their complaining attitude in the context of the Indian banking sector: non-complainers, switchers, prompt complainers and positive thinkers. Non-complainers tend not to complain because they do not know where and how to complain.…”
Section: How Much Personal Time and Effort Are Customers Willing To Imentioning
confidence: 99%
“…Following the segmentation created by Siddiqui and Tripathi (2010), first respondents were classified into non-complainers and complainers.…”
Section: Typology Of Customers On the Basis Of Their Complaining Behamentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, customers perceived that companies have a negative attitude towards complaint resolution (Lau & Ng, 2001). Siddiqui & Tripathi (2010) found four types of customers in terms of their complaining attitude in the context of the Indian banking sector: non-complainers, switchers, prompt complainers and positive thinkers, and the majority of the customers (61%) belonged to the noncomplaining group. They further found that many of the customers of the noncomplaining group do not know where and how to complain.…”
Section: Factors Affecting Consumers' Intention To Complainmentioning
confidence: 99%